School Performance and the Youth Labor Market - Murphy, Kevin M.; Peltzman, Sam (Journal of Labor Economics, 2004)
We estimate how 1970–90 changes in an outcome‐based measure of school quality (state average test scores) affected changes in earnings for those leaving high school to enter a state’s labor force. We find that a one standard deviation deterioration in a state’s relative test score performance is associated with a 3% (or .5 SD) reduction in average wages of young entrants to the labor force. We also find a similar decline in college matriculation. There is weak evidence that the school quality effect on earnings diminishes as labor force entrants acquire experience.